2017
DOI: 10.32582/aa.58.2.4
|View full text |Cite
|
Sign up to set email alerts
|

New records of the alien polychaete worm Chaetozone corona (Polychaeta: Cirratulidae) in the Adriatic Sea

Abstract: Several specimens of the alien polychaete Chaetozone corona were encountered at sites along the Italian coasts of the Adriatic Sea between 2006 and 2015, indicating its successful establishment in the area. Morphological variability between specimens from the North Adriatic and the South Adriatic was detected. Methyl Green staining patterns revealed further minor differences suggesting the presence of two slightly different populations. Chaetozone corona does not appear to be invasive in natural conditions, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…However, Çinar & Ergen (2007) suggested that past records (from 1989), wrongly assigned to Chaetozone setosa McIntosh, 1911, reached densities of 430 ind/m 2 . Grossi et al (2017) recorded the same species in muddy and sandy bottoms along the Adriatic coast, with densities of 30 ind/m 2 in north Adriatic and 500 ind/m 2 in the harbour of Bari. Other records made by Munari et al (2017) showed its occurrence in the Tyrrhenian sea.…”
Section: Alien Speciesmentioning
confidence: 80%
“…However, Çinar & Ergen (2007) suggested that past records (from 1989), wrongly assigned to Chaetozone setosa McIntosh, 1911, reached densities of 430 ind/m 2 . Grossi et al (2017) recorded the same species in muddy and sandy bottoms along the Adriatic coast, with densities of 30 ind/m 2 in north Adriatic and 500 ind/m 2 in the harbour of Bari. Other records made by Munari et al (2017) showed its occurrence in the Tyrrhenian sea.…”
Section: Alien Speciesmentioning
confidence: 80%